High-impact chronic pain : barriers and facilitators identified by Western Cape primary healthcare physiotherapists - Mason, Brett James Nairn (Stellenbosch : Stellenbosch University, 2023)
Thesis (MHumanRehabSt)--Stellenbosch University, 2023.